Examine the Influence of speech therapy with cognitive behavior therapy on reducing the severity of stuttering among stuttering patients of 18 years old and above in the city of Esfahan - Pegah Ansari; Bijan Shafie; Yousef Gorji (Vesnu Publications, 2013)
Abstract Introduction: The purpose of this research is to examine the influence of "speech therapy with cognitive behavior therapy" on reducing the severity of stuttering amongst stuttering patients of 18 years old and above in the city of Isfahan. Materials & Methods: The study used a quasi-experimental design with pretest - posttest control group. The sample group included 24 people suffering from stuttering who attended public speech therapy clinics of Isfahan. For the diagnosis and severity of stuttering, stuttering severity instrument (SSI4) was used. After doing the pre-test, subjects were placed into one experimental group of speech therapy with cognitive behavior therapy and one control group. Speech therapy for this research included ten 45-minutes sessions which was done for each individual subject and cognitive behavior therapy included ten 90-minutes group sessions. After finishing the therapy sessions, the post-test was done. In analyzing the data, Analysis of Covariance & Mann-Whitney U test were deployed. Results: Data analysis showed that speech therapy with cognitive behavior therapy has a significant impact on reducing the severity of stuttering. Conclusion: speech therapy with cognitive behavior therapy is effective in reducing stuttering. Key words: speech therapy- cognitive behavior therapy-stuttering